177k views
2 votes

(x)/(3) - 3 = (x)/(9) + 3what value of c make this equation true?

1 Answer

6 votes

The given expression:


(x)/(3)-3=(x)/(9)+3

Arrange the variables terms and constant term together:


\begin{gathered} (x)/(3)-3=(x)/(9)+3 \\ (x)/(3)-(x)/(9)=3+3 \end{gathered}

Least Common multiple of 3 & 9 is 9


\begin{gathered} (x)/(3)-(x)/(9)=3+3 \\ (3x-x)/(9)=6 \\ (2x)/(9)=6 \end{gathered}

Apply cross multiplication:


\begin{gathered} (2x)/(9)=6 \\ 2x=6*9 \\ x=(6*9)/(2) \\ x=27 \end{gathered}

Answer: J) 27

User Codnodder
by
6.1k points